Experimental investigation into the influence of low mass and heat fluxes and transient perturbances in vapour quality and heat flux on the behaviour of boiling R-245fa in horizontal pipes - Dirker, Jaco (University of Pretoria, 2022)
Thesis (PhD)--University of Pretoria, 2021.